Pregnancy Related Biometrical Changes in the Ovaries and Uterus of the Balami Sheep (Global Journal of Medical Research, 2014)
A pregnancy related biometrical study was carried out on ovaries and uterus of the Balami sheep in Maiduguri, Nigeria, with the aim of documenting information on it. Dimensions of 10 non-pregnant and 30 apparently normal pregnant Balami sheep ovaries and uteri obtained from the Maiduguri Municipal abattoir were analyzed. The length, diameter, thickness and weight of left ovary showed no significant increase along the stages of gestation while only the length of the right ovary showed very significant (p
Keywords: balami sheep; biometry; ovary; pregnancy; uterus